Visible-Light-Driven Denitrogenative C–C Bond Formation and Oxidative Difunctionalization of Vinyl Azides - Sardar, Santosh Sing; De, Aramita; Pal, Satyajit; Sarkar, Subhankar; Santra, Sougata; Zyryanov, Grigory V.; Majee, Adinath (Synlett, 2023)
A newer synthetic protocol has been developed to synthesize α-oxyalkyl ketones from vinyl azides under transition-metal-free reaction conditions. The reaction proceeds in the presence of organic photoredox catalyst rose bengal, an oxidant tert-butyl hydroperoxide (TBHP), and ethers. A broad range of substituted vinyl azides were found to react smoothly upon visible-light irradiation, which readily furnished the related products. Several control experiments have been done to suggest a probable mechanism. The process is initiated by radical addition to vinyl azide, which triggers a cascade fragmentation mechanism driven by the loss of dinitrogen and the stabilized ether radical ultimately produces the α-oxyalkyl ketones. This method provides a simple, mild, straight forward, novel paradigm to prepare α-oxyalkyl ketones.
Keywords: visible light; rose bengal; α-oxyalkyl ketones; oxidative difunctionalization; vinyl azides